National employment, migration and education in the GCC - Hertog, Steffen (Gulf Region: Economic Development and Diversification., 2012)
This volume provides a cross-cutting analysis of the policy challenges related to GCC labor markets. It analyzes the different dimensions of segmentation of these markets, factors of change influencing labor supply such as trends in education and demography, as well as the impact of potential future reforms in areas such as immigration policy, labor sponsorship, taxation and minimum wages. The work therefore provides an overview of what arguably will be the core socio-economic challenge for the GCC in the coming years.